Gibalne navade, stres in zadovoljstvo zaposlenih v zdravstvenem centru Aristotel v času epidemije COVID-19 - Udrih, Maruša (Šport (Ljubljana), 2022)
Physical activity enables healthcare professionals better management of physical and mental workload, which is important for productivity and quality work with patients. The aim of the research was to determine the state of physical activity of health professionals, their coping with stress and job satisfaction during the COVID-19 epidemic. We were also interested in the connections between movement habits, health assessment and experiencing stress. Health professionals (76 %) from health center Aristotel with an average age of 44,2 ± 14,4 years and an average 17,9 ± 12,2 years of service participated in the study. The results showed that health professionals are not physically active enough, as they do not meet the recommendations on the amount of weekly physical activity. We found that the main cause of stress is overwork and that workloads increased during COVID-19. However, we did not find an association between the amount of physical activity and health assessment, as well as not with experiencing stress. Employees have shown high satisfaction with their work environment and job, the level of motivation at work, the work and the range of tasks they perform, and the flexibility they have at work. This shows that health center Aristotel is a stimulating and motivating work environment, with a positive organizational climate and good interpersonal relationships.
Keywords: raziskave; stres; šport; telesna aktivnost; zadovoljstvo na delovnem mestu; zdravje